Experiences of Postpartum Depression in Women of Color. Issue 2 (March 2023) - Beck, Cheryl Tatano
Abstract: Purpose: To examine the experiences of postpartum depression among U.S.-born women of color via an integrative review. Study Design and Method: Databases searched were PubMed, CINAHL, Scopus, and PsycInfo. Sample inclusion criteria included qualitative research published in English that explored U.S.-born women of color's experiences of postpartum depression. There was no time limitation on when studies were published. Krippendorff's thematic content analysis method was used. Results: In this integrative review, eight qualitative studies investigating Black and Hispanic women's postpartum depression experiences and eight blog postings were synthesized. Five themes were identified that described postpartum depression experiences of Black and Hispanic women: (1) Struggling with an Array of Distressing Symptoms, (2) Cultural Stigma as a Powerful Roadblock, (3) Complicating Barriers to Seeking Much-Needed Professional Help, (4) Support as a Lifeline or "Just Pulling Yourself up by Your Bootstraps, " and (5) Preferences for Help with Postpartum Depression . Clinical Implications: Cultural stigma of mental illness plus lack of knowledge of postpartum depression were strong barriers to women of color seeking timely professional mental health care. Nurses can share information about perinatal mental illness with women in cultural communities to help decrease stigma and increase mental health literacy. All health care providers and policy makers need to focus attention on the impact that women of color's economic and social stressors have on their postpartum depression. Abstract : In this integrative review, cultural stigma of mental illness plus lack of knowledge of postpartum depression were found to be strong barriers to women of color seeking timely professional mental health care. Nurses can share information about perinatal mental illness to help decrease stigma and increase mental health literacy. All health care providers and policy makers must focus attention on the impact that women of color's economic and social stressors have on their postpartum depression.